1999
DOI: 10.3758/bf03210833
|View full text |Cite
|
Sign up to set email alerts
|

Do images involuntarily trigger search? A test of Pillsbury’s hypothesis

Abstract: Pillsbury (1908) suggested that deciding to search for something in a scene consists of nothing more than forming a visual image of the target. If so, imaging should trigger search even when it would be more advantageous not to search. Subjects were cued to form an image of a specified object (e.g., tiger) and to press a key when they had done so. This initiated the presentation of a sequence of pictures, with a single target digit interspersed; the subject's task was to report this digit. The sequence contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 16 publications
7
79
2
1
Order By: Relevance
“…This tendency illustrates what we have termed consonance-driven orienting. This finding is consistent with previous reports (Downing, 2000;Pashler & Shiu, 1999). However, the present work goes well beyond those studies in showing that consonance-driven orienting can play a decisive role in the control of attention.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This tendency illustrates what we have termed consonance-driven orienting. This finding is consistent with previous reports (Downing, 2000;Pashler & Shiu, 1999). However, the present work goes well beyond those studies in showing that consonance-driven orienting can play a decisive role in the control of attention.…”
Section: Discussionsupporting
confidence: 81%
“…When no competing top-down set is in place, it appears that consonance-driven orienting can easily play a decisive role in attention control: In Experiment 1B, the consonance-driven orienting increased the chance of reporting the critical shape from the chance level (33%) to 77%. The results also go beyond the work of Pashler and Shiu (1999) and Downing (2000) in showing that the effects "spread" to encompass inputs that are semantically related to the primes. In Experiment 2, in which prime and critical word were linked only by a semantic association, the probability still increased to 40%.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is generally agreed that the PFC plays a critical role in attention and working memory, which activation is positively correlated with the load of object WM [19]. Attention broadly participate in manipulation and updating of contents in working memory, and the temporary information preservation and manipulation in working memory are also essential components to attention, for example, some studies [20] showed that forming a visual image of a target will facilitate the visual search, in another words, the act of preparing to search might consist, not in some mental operation specific to search per se, but merely in forming a mental image of the target to be searched for. Anatomically studies indicate that mediate working memory and selective attention show a striking degree of overlap in neural substrates [21].…”
Section: Neuropsychological Studies Of Dlpfc Patients: Disorders Of Amentioning
confidence: 99%